O pewnych cechach stylistycznych poezji wielkich polskich romantyków - Śliwiński, Władysław (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The article analyses syntactic productivity of lexemes in nominal poetic constructions, i.e. in adjective-nominal constructions selected according to criteria of semantics, syntax, and usage. The corpus of texts from which these structures were excerpted consists of poetic texts by Adam Mickiewicz, Juliusz Słowacki, Zygmunt Krasiński and Cyprian Kamil Norwid. Adjectival and nominal lexemes were divided into monoproductive and polyproductive groups and four syntactically variant types were discovered as the result of their combination. A quantitative approach to these syntactic patterns brings to light stylistic differences and similarities appearing in the idiolects of the writers. Similar characteristics that differentiate or indicate likeness among the styles of the four analysed poets can be observed when analysing adjectives and nouns - the components of nominal poetic constructions which are subject to differential distribution (polydistributive and monodistributive) on the one hand and to genetic divergence based on poetic links existing before Romanticism or first introduced into poetry by the Romantics on the other.